Heidegger and Gadamer on the History of Being and the Relationship between Being and Language - Marino, Stefano (Scenari, 2021)
This paper takes up the issue of Gadamer’s “appropriation” of Heidegger’s later philosophy, and it does so in terms of an examination of some aspects of Heidegger’s Being-historical perspective that Gadamer seems to question and sometimes explicitly reject. I argue that Gadamer’s criticism of the later Heidegger is mostly based on an interpretation of Heidegger’s conception of the history of Being (Seinsgeschichte) as a form of philosophy of history which shares with Hegel’s Geschichtsphilosophie a genuinely eschatological self-consciousness that Gadamer, for his part, does not endorse. Given these assumptions, I finally try to highlight some consequences of Gadamer’s peculiar and “selective” reception of the later Heidegger in the realm of the philosophy of language, in particular with regard to the questions concerning the language of metaphysics and the relationship between Being and language.